Production of Hand Washing Soap from Ethanol Extract of Fern (Pteridophyta), Nampong Leaves (Siegesbeckia orientalis) and Thistle Plants (Calotropis gigantea) - Nuris Silvia; Shovi Amila (Journal of Natural Sciences and Mathematics Research, 2019)
Soap is an ingredient that comes from natural oils or fats reacting with caustic soda in the process known as lathering or saponification. Hand washing soap from fern (Pteridophyta) as the main ingredient is one of the antiseptic soaps that will be made, by comparing the drug Spirulina to determine the level of anti-bacteria produced. This study uses a hot process method with a soap heating time of about 20 minutes and a heating temperature of around 80°C. The results of testing the quality of hand washing soap as an antiseptic that meets the test standards are organoleptic test, acidity test (pH), foam resistance level test, and skin irritation test. So it's good to use as a hand sanitizer to get rid of bacteria and germs. ©2019 JNSMR UIN Walisongo. All rights reserved.